The Synergistic Effect of Layout Regularity (Seiton) and Inventory Data Accuracy on Pick-Up Time Efficiency: A Quantitative Study in i3L Laboratory Warehouse - Adiprasetyo, Wahyudi; Sunardhi, Yoseph (CV. Civiliza Publishing, 2025)
This study aims to analyze the synergistic effect of Seiton (systematic arrangement) and inventory data accuracy on the efficiency of item retrieval time in the i3L laboratory warehouse. A pre-post intervention design with multiple linear regression analysis was employed. Data were collected through 5S audits, distance measurements, time studies, and stock opname. Results showed significant improvements in Seiton scores (from 2.1 to 4.6), inventory accuracy (from 67% to 97%), and a reduction in retrieval time (from 1256 minutes to 45 minutes). Regression analysis indicated that both independent variables had a significant negative effect on retrieval time (p < 0.005), with an R² value of 0.78. This suggests that 78% of the variation in retrieval time can be explained by the combination of Seiton and data accuracy. The findings underscore the importance of integrating physical organization and data accuracy in warehouse management. It is recommended to implement 5S integrated with periodic data audits to support logistics efficiency and productivity.